2005
DOI: 10.1289/ehp.7374
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Exposure Alters Follicle-Stimulating Hormone Levels in Mexican Agricultural Workers

Abstract: Organophosphorous pesticides (OPs) are suspected of altering reproductive function by reducing brain acetylcholinesterase activity and monoamine levels, thus impairing hypothalamic and/or pituitary endocrine functions and gonadal processes. Our objective was to evaluate in a longitudinal study the association between OP exposure and serum levels of pituitary and sex hormones. Urinary OP metabolite levels were measured by gas–liquid chromatography, and serum pituitary and sex hormone levels by enzymatic immunoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 18 publications
2
40
1
1
Order By: Relevance
“…Epidemiological studies have linked exposure to OP (including Me-Pa) with decreased semen quality, increased sperm DNA damage and hormonal imbalance (Padungtod et al, 2000;Recio et al, 2001Recio et al, , 2005Sánchez-Peña et al, 2004). In addition, Me-Pa exposure caused testicular dysfunction (Narayana, 2006), reduced sperm quality (Mathew et al, 1992;Narayana et al, 2005), and increased sperm genetic damage (Narayana et al, 2005;Piña-Guzmán et al, 2006) in laboratory animals.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have linked exposure to OP (including Me-Pa) with decreased semen quality, increased sperm DNA damage and hormonal imbalance (Padungtod et al, 2000;Recio et al, 2001Recio et al, , 2005Sánchez-Peña et al, 2004). In addition, Me-Pa exposure caused testicular dysfunction (Narayana, 2006), reduced sperm quality (Mathew et al, 1992;Narayana et al, 2005), and increased sperm genetic damage (Narayana et al, 2005;Piña-Guzmán et al, 2006) in laboratory animals.…”
Section: Discussionmentioning
confidence: 99%
“…SG-adjusted TCPY and 1N concentrations were also both lntransformed. Inclusion of covariates was based on statistical and biologic considerations (34). Age and BMI were modeled as a continuous variable, smoking status was dichotomized by current smoker versus never smoked or former smoker, and race was categorized into four groups: white, African American, Hispanic, and other.…”
Section: Discussionmentioning
confidence: 99%
“…It also explains the increased number of females complaining of dysfunctional uterine bleeding in those exposed to pesticides [15] showed negative associations between OP exposure and serum levels of FSH and LH in Mexican agricultural workers, but they did not observe significant associations between testosterone or estradiol serum levels and urinary OP metabolites [21] reported that in adult men, an inverse association exists between urinary levels of OP and CB metabolites and serum LH and testosterone levels.…”
Section: Helping In Farming Operationsmentioning
confidence: 97%
“…OPs are suspected to alter reproductive function by reducing brain acetylcholinesterase (AChE) activity and secondarily influencing the gonads. Experiments on animals have shown that repeated doses of OP significantly decreased brain AChE activity and significantly increased acetylcholine, gamma-aminobutyric acid, epinephrine, norepinephrine, dopamine, and 5-hydroxyttyptamine concentrations, altering reproductive function by reducing brain acetylcholinesterase activity and monoamine levels, thus impairing hypothalamic and/or pituitary endocrine functions and gonadal processes [15].…”
Section: Helping In Farming Operationsmentioning
confidence: 99%